RETRACTED: Metallic Ions Encapsulated in Electrospun Nanofiber for Antibacterial and Angiogenesis Function to Promote Wound Repair - Zhu, Chenxi; Cao, Runfeng; Zhang, Yu; Chen, Ru (Frontiers in Cell and Developmental Biology, 2021)
Electrospun nanofiber is an attractive biomaterial for skin tissue engineering because it mimics the natural fibrous extracellular matrix structure and creates a physical structure suitable for skin tissue regeneration. However, endowing the nanofibrous membranes with antibacterial and angiogenesis functions needs to be explored. In the current study, we aimed to fabricate gelatin/polycaprolactone (GT/PCL) (GT/PCL-Ag-Mg) nanofibers loaded with silver (Ag) and magnesium (Mg) ions for antibacterial activity and pro-angiogenesis function for wound repair. The fabricated GT/PCL membranes had a nanofibrous structure with random arrangement and achieved sustained release of Ag and Mg ions. In vitro results indicated that the GT/PCL-Ag-Mg membranes presented satisfactory cytocompatibility with cell survival and proliferation. In addition, the membranes with Ag demonstrated good antibacterial capacity to both gram-positive and gram-negative bacteria, and the Mg released from the membranes promoted the tube formation of vascular endothelial cells. Furthermore, in vivo results demonstrated that the GT/PCL-Ag-Mg membrane presented an accelerated wound healing process compared with GT/PCL membranes incorporated with either Ag or Mg ions and pure GT/PCL alone. Superior epidermis formation, vascularization, and collagen deposition were also observed in GT/PCL-Ag-Mg membrane compared with the other membranes. In conclusion, a multifunctional GT/PCL-Ag-Mg membrane was fabricated with anti-infection and pro-angiogenesis functions, serving as a potential metallic ion-based therapeutic platform for applications in wound repair.